Investigating oxygen reduction pathways on pristine SOFC cathode surfaces by in situ PLD impedance spectroscopy. Issue 5 (23rd November 2021) - Siebenhofer, Matthäus; Riedl, Christoph; Schmid, Alexander; Limbeck, Andreas; Opitz, Alexander Karl; Fleig, Jürgen; Kubicek, Markus
Abstract : Temperature and p (O2 ) dependences of the oxygen exchange kinetics of SOFC cathode materials were correlated with point defect concentrations. Defect chemical contributions were identified as a major part of effectively measured activation energies. Abstract : The oxygen exchange reaction mechanism on truly pristine surfaces of SOFC cathode materials (La0.6 Sr0.4 CoO3− δ = LSC, La0.6 Sr0.4 FeO3− δ = LSF, (La0.6 Sr0.4 )0.98 Pt0.02 FeO3− δ = Pt:LSF, SrTi0.3 Fe0.7 O3− δ = STF, Pr0.1 Ce0.9 O2− δ = PCO and La0.6 Sr0.4 MnO3− δ = LSM) was investigated employing in situ impedance spectroscopy during pulsed laser deposition (i-PLD) over a wide temperature and p (O2 ) range. Besides demonstrating the often astonishing catalytic capabilities of the materials, it is possible to discuss the oxygen exchange reaction mechanism based on experiments on clean surfaces unaltered by external degradation processes. All investigated materials with at least moderate ionic conductivity ( i.e. all except LSM) exhibit polarization resistances with very similar p (O2 )- and T -dependences, mostly differing only in absolute value. In combination with non-equilibrium measurements under polarization and defect chemical model calculations, these results elucidate several aspects of the oxygen exchange reaction mechanism and refine the understanding of the role oxygen vacancies and electronic charge carriers play in the oxygen exchange reaction. It was found that a major part of the effective activation energy of the surface exchange reaction, which is observed during equilibrium measurements, originates from thermally activated charge carrier concentrations. Electrode polarization was therefore used to control defect concentrations and to extract concentration amended activation energies, which prove to be drastically different for oxygen incorporation and evolution (0.26 vs. 2.05 eV for LSF).